Short signatures — our headache - Jonaitienė, Nijolė (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
It is difficult to imitate another persons signature. Handwritten signature is unique. There are no special rules for person‘s signature. The signature can be any. It only should meet the requiments: consist of letters not only loop, line, curve and etc. elements. Unfortunately, in our hurried age signatures become shorter and simpler. During that time people lost emotional connection to their signature. Many of the signatures of the high officials, who usually sign very important documents, are also very simple and sometimes seem more like graphical pictures than signatures. We receive many short and too simple signatures recently. It is a real headache for Lithuanian handwriting experts. Modern handwriting examinations are powerless to solve this problem. It is our duty to inform people about the dangers of short signatures and to educate people to sign accordance with a person’s surname. This would contribute to the signing culture growth, and as a result would let us answer and help in more cases.
Keywords: too simple signature; literal signature; illegible elements; mixed signature; monogram; graphical picture; historical circumstances; irresponsible approach to falsification protection